2009
DOI: 10.1111/j.1524-4725.2009.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Blind Multicenter Study of the Efficacy and Safety of Injections of a Commercial Preparation of Botulinum Toxin Type A Reconstituted up to 15 Days Before Injection

Abstract: The results confirm the possibility of injecting 500 U of BT-A up to 15 days after its reconstitution safely and without loss of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…After cold storage of reconstituted BT-A for 2 weeks, the toxin has been shown to retain its efficacy and time of onset in the treatment of lateral periorbital rhytids 11 (crow's feet), horizontal forehead rhytids, 13 and glabellar rhytids. 12 The follow-up periods in these studies ranged from 3 to 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After cold storage of reconstituted BT-A for 2 weeks, the toxin has been shown to retain its efficacy and time of onset in the treatment of lateral periorbital rhytids 11 (crow's feet), horizontal forehead rhytids, 13 and glabellar rhytids. 12 The follow-up periods in these studies ranged from 3 to 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with one of the longest periods of refrigerator storage, no bacterial contamination was identified after 10 months. 12 Together, these studies provide solid evidence that BT-A reconstitution and storage for periods significantly longer than suggested by the manufacturers is both safe and clinically effective, and commonplace in clinical practice. Our recommendation for the storage and use of BT-A for 2 weeks after reconstitution is based on the numerous studies demonstrating preserved toxin efficacy after a 2-week storage period.…”
Section: Bt-a: Botulinum Toxin Type a Cdc: Centers For Disease Contromentioning
confidence: 94%
See 1 more Smart Citation
“…However, in some studies it has shown that toxin's efficacy remains same until 15 days after reconstitution and no bacterial contamination occurs. 28 Despite of some adverse effects and reversibility of BTX-A via regeneration of nerve-muscle complex and SNAP-25 proteins, BTX-A injections seems to be the least invasive treatment option for gummy smile cases.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is for sterility and efficacy purposes. Recent studies have shown that toxin efficacy remains the same until 15 days after reconstitution, and bacterial contamination does not take place 20 .…”
Section: Dosage and Administrationmentioning
confidence: 99%